Clinical utility and prognostic implications of the 4S‐AF scheme: Report from Asia Pacific Heart Rhythm Society Atrial Fibrillation Registry. (22nd June 2022) - Chao, Tze‐Fan; Tse, Hung‐Fat; Teo, Wee‐Siong; Park, Hyung‐Wook; Shimizu, Wataru; Chen, Shih‐Ann; Lip, Gregory Y. H.
Abstract: Background: The 4S‐AF classification scheme comprises of four domains (stroke risk [St], symptoms [Sy], severity of atrial fibrillation (AF) burden [Sb] and substrate [Su]), which has been recommended in the 2020 ESC guidelines to characterize and evaluate patients with AF. Objectives: We aimed to determine whether the 4S‐AF scheme would be useful for AF characterization and provides prognostic information in a large contemporary prospective Asian registry conducted by the Asia Pacific Heart Rhythm Society (APHRS). Methods: Among 4666 patients enrolled in APHRS registry, 3586 of them whose data about left atrial (LA) dimension and European Heart Rhythm Association (EHRA) symptom score were available have constituted as the study population. The 4S‐AF score was calculated as the sum of each domain with a maximum score of 9. The clinical endpoint was defined as the 1‐year composite risk of any thromboembolic event, ischaemic stroke, heart failure, acute coronary syndrome, significant coronary artery disease requiring coronary intervention and all‐cause mortality. Results: Based on the 4S‐AF domains, 86.7% were 'non‐low risk' for stroke; 94.3% had EHRA Class I‐II, 48.5% were newly diagnosed or paroxysmal AF; and only 8.4% had no cardiovascular risk factors or LA enlargement. The risk of clinical events was higher in patients who were 'non‐low risk' for stroke (aOR 2.175, 95% CI 1.060–4.461), with permanent AF (aOR 1.579, 95% CI 1.106–2.225) and increasing points for substrate (aORs 2.376–4.968 from score 2 to 4). When compared to the first tertile of 4S‐AF score (0–3 points), patients in the second tertile (4–5 points) had approximately 2.5‐fold increase in adverse events (OR 2.478, 95% CI 1.678–3.661, p  < .001), while those in the third tertile (6–9 points), had a 3.5‐fold increase (OR 3.484, 95% CI 2.322–5.226, p  < .001), both without significant differences between the 5 participating countries ( p for interaction > .05). If all 4S‐AF domains were appropriately treated, this was associated with a lower risk of composite clinical outcomes (aOR 0.384, p  < .001; p for interaction for different countries = .234). Conclusions: Categorization according to the 4S‐AF scheme can be related to the risk of the composite adverse event rate in Asian AF patients, and appropriate treatments based on the 4S‐AF scheme resulted in better clinical outcomes. These observations support the characterization and management according to the 4S‐AF scheme in Asian patients.